Differentiated Learning as a Humanistic Approach to Improving the Quality of Education in Indonesian Context - Dewa Ayu Made Ratih Putri Wijaya; Putu Adi Krisna Juniarta; Gede Mahendrayana (The Art of Teaching English as a Foreign Language (TATEFL), 2025)
This study aims to examine the application of differentiated learning as a humanistic approach to improving the quality of education in Indonesia. The study was conducted using a systematic literature review using the PRISMA approach of sixteen scientific articles published between 2022 and 2025. Article selection was based on specific inclusion criteria, while methodological quality was assessed using the Joanna Briggs Institute (JBI) instrument. The review results indicate that differentiated learning can strengthen student engagement, foster learning motivation, and improve academic achievement by adapting materials, methods, and evaluation formats to student needs. The humanistic approach, which emphasizes empathy, freedom, and respect for individual potential, has proven to be a key element in the success of this strategy. Teachers, acting as facilitators, contribute significantly to creating an open and inclusive learning climate. Although its implementation still faces obstacles such as limited resources, uneven teacher understanding, and the digital divide, the Independent Curriculum policy provides innovative space for its development. The integration of humanitarian values, technological advancements, and school collaboration is the foundation for sustainable educational transformation. Thus, differentiated learning reflects an educational paradigm that is more adaptive, inclusive, and oriented towards holistic human development.